PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN - Rahmadhanty Kusuma Astari; Darsono Darsono (Diponegoro Journal of Accounting, 2020)
This study was aimed to examine the effect of intellectual capital on company performance. The independent variables used in this research are intellectual capital consists of HCE (Human Capital Efficiency), SCE (Structural Capital Efficiency, and CEE (Capital Employed Efficiency). This study used secondary data in the form of annual report collected through the Indonesia Stock Exchange (IDX). This research used purposive sampling method. The sample of this study consisted of 143 companies listed on the Indonesia Stock Exchange (IDX) out of a population of 308 samples in the period of 2016-2018. This study applied multiple regression analysis. The results showed that Structural Capital Efficiency (SCE) and Capital Employed Efficiency (CEE) has a positive effect on company performance. However, Human Capital Efficiency (HCE) has negative effect on company performance.